Duration of Hospitalization and Risk Factors of Readmission of Community-Acquired Pneumonia Incidence in Hospitalized Toddlers - Lisa, Corina; Arini, Merita (Jurnal Respirologi Indonesia, 2024)
Background: The Indonesia Health Profile Report 2020 stated that pneumonia is one of the causes of high infant and toddler mortality in Indonesia. Length of stay and readmission are crucial indicators of service quality for hospitalized pneumonia patients. This study aims to determine the duration of hospitalization and identify risk factors for readmission among toddlers hospitalized with CAP.Methods: This cross-sectional study was conducted with subjects of pneumonia toddlers hospitalized in Sarila Husada Hospital Sragen from November 2021 to Januari 2023Results: A total of 357 toddlers were hospitalized with CAP (median age = 17 months; IQR 7–24); the majority were under 36 months old (309 subjects; 86%); male (54%) predominated than female (46%). Median duration of hospitalization for CAP=2 days with IQR=3.0-5.0. Readmission events were only 5, higher among toddlers aged 2-36 months but not statistically significant. Factors associated with readmission in CAP toddlers were the history of previous hospitalizations during the past year due to infection (P=0.012; adjusted odds ratio [aOR]=13.6; confidence interval [CI]=1.49–12.34).Conclusion: The readmission rate was very low in our study. Toddlers 2–36 months of age and those with previous hospitalizations with infections are at higher risk of readmission in CAP.